Relationship between Nurse Response Time and Accuracy of Triage in the Emergency Room - Hardianto; Wiyadi; Hesti Prawita Widiastuti (Formosa Journal of Applied Sciences, 2023)
This study aims to identify and analyze the relationship between nurse response time and triage accuracy in the IGD RSUD dr. Abdul Rivai Berau District. This research is a type of analytic observational research with a cross sectional design. The research sample consisted of 25 nurses taken by total sampling in the emergency room of RSUD dr. Abdul Rivai. Non-parametric data analysis was performed using the Fisher Exact test with a significance level of 0.05. Nurse Response Time in the Emergency Room of RSUD dr. Abdul Rivai, Berau Regency, the majority acted responsively as many as 16 respondents (64.00%) and right in triage as many as 17 respondents (68.00%). There is a significant relationship between nurse response time and triage accuracy in the emergency room of RSUD dr. Abdul Rivai Berau District (Sig = 0.022; Risk Estimate = 0.500).